INCREASING THE OBJECTIVITY OF WRITING SKILLS ASSESSMENT: RUBRIC INTEGRATION AND CONSTRUCTIVE FEEDBACK - Bayu Indarko (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Assessment of students' writing skills often faces subject-related challenges that interfere with the effectiveness and efficiency of learning. This article examines the effectiveness of using rubrics and constructivist approaches to improve the objectivity of the writing process. Through a study of the educational literature, it was concluded that the rubric provides clear and concise evaluation criteria, which can reduce teacher bias and improve evaluation consistency. Specific, well-structured feedback helps students understand their own strengths and weaknesses in writing while also providing specific guidance for improvement. The integration of feedback and rubrics creates an evaluation system that is more transparent, fair, and focused on student growth. The application of these two instruments has so far resulted in issues such as time constraints and teacher skills. Innovative strategies, such as student participation in rubric development and the use of feedback-based revision sessions, as an effective solution